Pathogenesis of Chronic Pancreatitis. (1st February 1989) - Sarles, H; Bernard, J.P.
Abstract : Studies from the Marseille group allowed differentiation of acute pancreatitis (a group of lesions secondary to either extrapancreatic causes such as gallstones or to pancreatic diseases such as cancer and chronic pancreatitis), from chronic pancreatitis. Two forms of chronic pancreatitis arc easily distinguished: obstructive pancreatitis secondary to pre-existing obstruction on pancreatic ducts (tumours, scars, etc); and the most frequent disease, chronic calcifying pancreatitis, which is a pancreatic lithiasis due to a double phenomenon. This double phenomenon is the precipitation of insoluble calcium salts and the precipitation of degraded fragments of a newly discovered secretory protein known as pancreatic stone protein (PSP). This family of glycoproteins, the amino acid sequence of which has been established, is synthesized by the pancreatic acinar cell and its biosynthesis is decreased in patients presenting with chronic calcifying pancreatitis. The secretory form of PSP prevents the formation of calcium salt crystals in the pancreatic juice which is normally supersaturated in calcium. Though the lesions and the secretory modifications of PSP are common to all forms of chronic calcifying pancreatitis, there are different etiological forms of the disease; alcoholic, tropical, hypercalcemic, hereditary and idiopathic. Alcohol consumption acts on pancreatic secretion by different mechanisms and is responsible for an increased secretion of secretory protein (enzymes) due to cholinergic, vagal reflexes sensitive to ethanol. Alcohol consumption is generally associated with protein rich and either fat rich or fat poor diets, both of which are risk factors. Hypercalcemia also increases the secretion of protein and the viscosity of pancreatic juice. The tropical form is not due, as previously suggested, to cassava (manioc) consumption or kwashiorkor, but it is endemic in populations submitted to fat poor, protein poor diets. These etiological factors are only acting on predisposed patients. This suggests chat a low or abnormal biosynthesis of PSP is responsible for the predisposition.